Epstein-Barr Virus-Encoded Small RNAs (EBERs) Are Present in Fractions Related to Exosomes Released by EBV-Transformed Cells - Ahmed, Waqar (Public Library of Science, 2014)
Epstein-Barr virus (EBV) is an oncogenic herpesvirus associated with a number of human malignancies of epithelial and lymphoid origin. However, the mechanism of oncogenesis is unclear. A number of viral products, including EBV latent proteins and non-protein coding RNAs have been implicated. Recently it was reported that EBV-encoded small RNAs (EBERs) are released from EBV infected cells and they can induce biological changes in cells via signaling from toll-like receptor 3. Here, we investigated if these abundantly expressed non-protein coding EBV RNAs (EBER-1 and EBER-2) are excreted from infected cells in exosomal fractions. Using differential ultracentrifugation we isolated exosomes from three EBV positive cell lines (B95-8, EBV-LCL, BL30-B95-8), one EBER-1 transfected cell line (293T-pHEBo-E1) and two EBV-negative cell lines (BL30, 293T-pHEBo). The identity of purified exosomes was determined by electron microscopy and western blotting for CD63. The presence of EBERs in cells, culture supernatants and purified exosomal fractions was determined using RT-PCR and confirmed by sequencing. Purified exosomal fractions were also tested for the presence of the EBER-1-binding protein La, using western blotting. Both EBER-1 and EBER-2 were found to be present not only in the culture supernatants, but also in the purified exosome fractions of all EBV-infected cell lines. EBER-1 could also be detected in exosomal fractions from EBER-1 transfected 293T cells whilst the fractions from vector only transfectants were clearly negative. Furthermore, purified exosomal fractions also contained the EBER-binding protein (La), supporting the notion that EBERs are most probably released from EBV infected cells in the form of EBER-La complex in exosomes.